AgNPs treatment reduces time recovery and increases bacterial sensitivity to antibiotics in cow´s purulent catarrhal endometritis. A translational study - Alejandro Huerta-Saquero; Ekaterina Nefedova; Nikolay N. Shkil; Alexey Pestryakov; Nina Bogdanchikova (PLoS ONE, 2025)
Cow purulent catarrhal endometritis (PCE) is a common reproductive disorder in dairy cattle caused by bacterial infections. PCE impacts fertility, milk production, and animal health. Therapeutic approaches include systemic or intrauterine antibiotics. Unfortunately, the overuse of antibiotics in treating PCE drives the emergence of antibiotic-resistant bacteria, making infections difficult to treat and increasing food safety concerns due to antibiotic residues remaining in milk and meat products, posing health risks to consumers. Antimicrobial nanomaterials, particularly silver nanoparticles (AgNPs), provide an efficient alternative to combat multi-resistant bacteria, and the synergistic activity of AgNPs and antibiotics has been well documented, making the treatments of bacterial infections more efficient. Here, a comparative study is shown applying Argovit-C (AgNPs) and Enrocide as therapeutics for treating PCE in cattle. Intrauterine application of Argovit-C reduces the recovery time of cattle in comparison with Enrocide treatment as well as increases the sensitivity to antibiotics of Escherichia coli isolates from cervical canal secretion samples of diseased cattle. The increased sensitivity was found to 24 antibiotics, including aminoglycosides, fluoroquinolones, tetracyclines, penicillins, cephalosporins, macrolides, polymyxin, rifampicin, and chloramphenicol. The increased sensitivity was much higher for those bacteria that did not show an active efflux effect. Furthermore, Argovit-C reduced the acquisition of blaDHA and blaGES resistance genes in E. coli , as well as the number of bacterial isolates without efflux effect. Overall, this translational study performed in 300 cows demonstrates the ability of Argovit-C AgNPs to combat bacterial infections, favoring an increase in bacterial susceptibility to antibiotics and reducing their ability to acquire antibiotic multi-resistant genes.